The Role of Genetics and Synergistic Effect of Targeting Common Genetic Mutations in Acute Lymphoblastic Leukemia (ALL) - Pilehvari, Niloofar; Katoueezadeh, Maryam; Hassanshahi, Gholamhossein; Torabizadeh, Seyedeh A.; Torabizadeh, Seyed Mohammad (Mini Reviews in Medicinal Chemistry, 2023)
Increasing concern regarding non-treatment and relapse in Acute Lymphoblastic Leukemia (ALL) among children and adults has attracted the attention of researchers to investigate the genetic factors of ALL and discover new treatments with a better prognosis. Nevertheless, the survival rate in children is more than in adults; therefore, it is necessary to find new potential molecular targets with better therapeutic results. Genomic analysis has enabled the detection of different genetic defects that are serious for driving leukemogenesis. The study of genetic translocation provides a better understanding of the function of genes involved in disease progression. This paper presents an overview of the main genetic translocations and dysregulations in the signaling pathways of ALL. We also report the inhibitors of these main translocations and evaluate the synergistic effect of chemical inhibitors and gamma-ray irradiation on ALL.
Keywords: gamma-ray irradiation